Hubungan Pengetahuan Dengan Sikap Remaja Dalam Pencegahan Keracunan Makanan Di Wilayah Kerja Puskesmas Padang Serai Kota Bengkulu Tahun 2025 - Dwi Putri Bunga Rizqi; Diyah Tepi Rahmawati; Danur Azissah RS (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Food poisoning is a health problem that still frequently occurs among adolescents, mainly due to a lack of knowledge and attitudes in implementing food safety. Adolescents tend to consume unhygienic street foods, thus increasing the risk of food poisoning. The purpose of this study was to determine the relationship between knowledge and attitudes of adolescents in preventing food poisoning in the working area of the Padang Serai Community Health Center, Bengkulu City in 2026. This research method is quantitative with a cross-sectional research design. The sampling technique used total sampling. The research instrument used a questionnaire on knowledge and attitudes about preventing food poisoning. Data analysis was carried out univariately and bivariately using appropriate statistical tests to determine the relationship between knowledge and attitude variables. The results of the univariate analysis showed that most respondents had a sufficient level of knowledge and attitudes in preventing food poisoning. The results of the bivariate analysis showed a significant relationship between knowledge and attitudes of adolescents in preventing food poisoning with a p-value <0.05, so Ho was rejected. This indicates that the better the level of adolescent knowledge, the more positive the adolescent's attitude in preventing food poisoning. Researchers suggest that the Padang Serai Community Health Center increase health promotion and education activities for adolescents regarding food safety and the prevention of food poisoning through counseling, information media, and collaboration with schools and the community, thereby increasing knowledge and forming positive attitudes among adolescents in preventing food poisoning.